PENGUATAN IDENTITAS KEMUHAMMADIYAHAN SISWA MELALUI PENDEKATAN LITERASI DAN TEKNOLOGI DIGITAL - Badrut Tamami; Yerry Mijianti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The development of digital technology has brought significant changes to the way millennials learn. Students not only obtain information from teachers, but also through social media, digital platforms, and virtual environments. This condition requires a learning model that is able to synergize Islamic values with digital competence. Departing from the strategic role of Al-Islam and Muhammadiyah Education (AIK) in Muhammadiyah schools, there is a need to develop a holistic learning approach that not only emphasizes the cognitive aspect, but also the affective, spiritual, and social behavior of students. MI Muhammadiyah 1 Tanjungrejo Wuluhan, as an educational institution based on organizational values, faces challenges in maintaining the consistency of Islamic character formation in the midst of digital culture penetration. Therefore, it is necessary to examine how AIK's holistic learning model can be applied effectively in the digital context to be in line with the needs of the character development of the millennial generation. In general, this study aims to: Analyze the needs of AIK's holistic learning model in the digital era in shaping the Islamic character of MI Muhammadiyah 1 Tanjungrejo Wuluhan students. Identify the current implementation and practice of AIK learning along with its strengths and weaknesses. Formulate an effective digital-based AIK holistic learning model for the millennial generation. Describe the impact of the learning model on the formation of students' Islamic character. This research uses a qualitative approach with a case study design at MI Muhammadiyah 1 Tanjungrejo Wuluhan. Needs Analysis Concept. Description of the learning context of AIK and the use of technology.